A method development randomised clinical study investigating efficacy of an experimental oral rinse in providing long-term relief from dentinal hypersensitivity. Issue 2 (November 2019) - Milleman, Kimberly R.; Milleman, Jeffery L.; Young, Sarah; Butler, Andrew; Araga, Mako; Atassi, Mounir
Abstract: Objectives: To evaluate and compare clinical efficacy of a 1.5% dipotassium oxalate monohydrate (KOX)-containing oral rinse ('Test') for the relief of dentinal hypersensitivity (DH) against Negative Control and Placebo oral rinses, adjunctive to twice-daily brushing with a standard fluoride dentifrice, after 8 weeks. Methods: This was a randomised, examiner blind, parallel-group, method development study in participants with DH, assessed at baseline and after 4 and 8 weeks by response to an evaporative (air) stimulus (evaluated by Schiff sensitivity score and a 10-point visual rating scale [VRS]) and a tactile stimulus (Yeaple probe). To boost compliance, study features included recruiting only regular oral rinse users, use of an oral rinse during acclimatisation, weekly supervised rinsing and twice-daily text reminders. Results: After 8 weeks, adjusted mean change from baseline in Schiff sensitivity score was significantly lower in the Test rinse group (n = 43) versus the Negative Control group (n = 23) (difference: −1.22; 95% CI −1.657, −0.782); tactile threshold score was significantly higher in the Test rinse group compared to the Negative Control rinse (difference: 37.46 g; 95% CI: 22.916, 51.995). Similar significant differences in Schiff/tactile scores were also demonstrated after 4 weeks use, after 4 and 8 weeks use as assessed by VRS and as compared to the Placebo rinse (n = 23) in all instances. Study products were generally well tolerated. Conclusions: The Test rinse showed statistically significant improvements in DH compared to the Negative Control and Placebo rinses after 8 weeks twice daily use. Compliance with the rinsing regimen and study visits was excellent. Clinical significance: Additional compliance features incorporated into this dentinal hypersensitivity study – recruitment of regular oral rinse users only, acclimatisation rinse, weekly supervised rinsing at the study site, twice-daily text reminders – appear to have been of benefit to the overall study design as compliance was high, and primary and secondary objectives were met.